The Effect Of Technology And Administrative Automation On Employees’ Work Life Quality (Case Study: Department Of Youth And Sports Of Kermanshah Province) - Keshtmand, Zahra; Nowrozian, Mohammad; Hatami, Khidan (The Turkish Online Journal of Design Art and Communication, 2016)
The aim of this study was to evaluate the Effect of technology and administrative automation on Employees’ work life quality of Directorate General of Youth and Sports Kermanshah province. This research is descriptive-correlation method that has been conducted as a field study. The statistic population was the General Directorate of Youth and Sports in Kermanshah province which their number was 125. Morgan table was used to determine sample sizes of 95 patients were randomly selected to participate. To collect data, a questionnaire Adel automation (2008), and the quality of working life and Walton (1973) were used. Validity was confirmed by experts. Reliability of questionnaires were obtained α = 0/92 for administrative automation and α = 0/76 for quality of working life by Cronbach alpha. To analyze the data, the Kolmogorov-Smirnov test was used, Pearson was performed using SPSS version 22. The results showed that the use of technology and administrative automation has a significant positive effect on the quality of working life of employees in the General Directorate of Youth and Sports in Kermanshah province.
Keywords: technology; administrative automation; quality of working life; employees